A Critical Review of Research and Policy in Youth-Focussed Housing First - McParland, Katherine; Rousseau-Thomas, Jayla; Waegemakers Schiff, Jeannette (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2019)
The Housing First approach is a social policy directive for addressing homelessness, but there is a lack of clear evidence of its effectiveness with youth experiencing homelessness. At the community level, service providers are implementing “youth-focussed Housing First” without the research support to evaluate the efficacy of this approach in providing stable housing that promotes a positive transition to adulthood. This comprehensive literature review includes ten of the most widely used social services databases, confirming a deficit of diverse perspectives and research evidence such as evaluative studies and peer reviewed articles validating the Housing First approach with youth. A comprehensive review of grey literature was also completed to determine what is known about youth-focussed Housing First and the most significant gaps in research. This article sets out directions for future research and produces social policy recommendations for all levels of Canadian government that will support Housing First programs that meet the unique developmental needs of youth. At the grassroots level, communities are adapting the Housing First approach to youth; this needs to be recognized and supported by research that evaluates the impact these programs are having in the lives of young people in order to inform scalability efforts to work towards eradicating youth homelessness. The hope is that youth-focussed Housing First develops a robust discussion in academic research. Résumé L’approche Logement d’abord est une directive de politique sociale visant à lutter contre l’itinérance, cependant, son efficacité n’est pas clairement démontrée auprès des jeunes en situation d’itinérance. Au niveau communautaire, les fournisseurs de services mettent en œuvre un programme « Logement d’abord » pour les jeunes malgré le manque d’études pour évaluer l’efficacité de cette approche afin de fournir aux jeunes un logement stable qui favorise une transition positive vers l’âge adulte. Cet article de revue détaillé inclut dix des bases de données de services sociaux les plus utilisées, ce qui aide à confirmer le manque de perspectives variées et de données de recherche telles que des études d’évaluation et des articles examinés par des pairs afin de valider l’approche « Logement d’abord » pour les jeunes. Une analyse détaillée de la documentation parallèle a également été réalisée afin de déterminer ce que l’on sait des programmes Logement d’abord pour les jeunes et les principales lacunes de la recherche. Cet article conçoit les orientations des futures études et présente des recommandations de politique sociale à tous les niveaux du gouvernement canadien, qui soutiendront les programmes Logement d’abord afin de répondre aux besoins développementaux uniques des jeunes. Au niveau local, les communautés adaptent l’approche Logement d’abord aux jeunes. Cela doit être reconnu et soutenu par des études qui évaluent l’impact de ces programmes sur la vie des jeunes afin de guider les efforts d’extensibilité visant à éradiquer l’itinérance des jeunes. Le but est de susciter une discussion animée en matière de la recherche universitaire quant au programme Logement d’abord pour les jeunes Mots clés: Jeunes; logement d’abord; logement d’abord pour les jeunes; article de revue